1980
DOI: 10.1029/ja085ia05p02108
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal oscillations of plasma within the Io torus

Abstract: We calculate the equilibrium latitude and the period of oscillations about this equilibrium latitude for plasma in a centrifugally dominated tilted dipole magnetic field representing Jupiter's inner magnetosphere. For a hot plasma the equilibrium latitude is the magnetic equator; for a cold plasma it is the centrifugal equator; for a warm plasma it is somewhere in between. In the small-tilt-angle approximation, the latitudinal oscillation period of a cold particle in the centrifugal potential field is Po = Pj/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 27 publications
(23 reference statements)
1
23
0
Order By: Relevance
“…and bounce velocities can be substantial. It is well-established (Cummings et al, 1980) that ions formed at maximum magnetic latitudes (±7°) will fall toward the plasma equator due to centrifugal and magnetic forces. Such ions have speeds of .....,12 km sec-1 at the plasma equator, but vanishingly small velocities when they return to Io's position at higher magnetic latitude.…”
Section: B3 Two-step Charge Exchange: Alternate Source Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…and bounce velocities can be substantial. It is well-established (Cummings et al, 1980) that ions formed at maximum magnetic latitudes (±7°) will fall toward the plasma equator due to centrifugal and magnetic forces. Such ions have speeds of .....,12 km sec-1 at the plasma equator, but vanishingly small velocities when they return to Io's position at higher magnetic latitude.…”
Section: B3 Two-step Charge Exchange: Alternate Source Processesmentioning
confidence: 99%
“…The plasma torus is known to be nonuniform (Morgan, 1985;Cummings et al, 1980), and it is possible that random clumps of plasma ten times denser than normal can bounce coherently along field lines for extended periods. We originally proposed that the jets were generated by 200 the interaction of such clumps with the extended neutral clouds (Schneider et al, 1984), but this explanation no longer appears likely.…”
Section: B3 Two-step Charge Exchange: Alternate Source Processesmentioning
confidence: 99%
“…Cummings et al (1980) showed that the field-aligned motion of picked-up ions could be approximated as a simple harmonic oscillation and that the period of oscillation could be described as a function of v gyro . Schneider et al (1991) estimated that the period of field-aligned oscillation was ∼5.6 h, which corresponds to a gyrovelocity of ∼13 km/s.…”
Section: Band-shaped Distributionmentioning
confidence: 99%
“…In the molecular ion destruction process, newborn picked-up ions swept downstream of Io begin a coherent bouncing motion along Jupiter's magnetic field line (Cummings et al, 1980). The velocity of the ions is described as…”
Section: Source Mechanisms Of Sodium Atomsmentioning
confidence: 99%
See 1 more Smart Citation